CD4 T cell responses to a variant antigen of the malaria parasite Plasmodium falciparum, erythrocyte membrane protein-1, in individuals living in malaria-endemic areas. - Allsopp, C; Sanni, L; Reubsaet, L; Ndungu, F; Newbold, C; Mwangi, T; Marsh, K; Langhorne, J (2002)
Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP-1) is a variant antigen on the surface of malaria-infected red blood cells. Antibody responses to PfEMP-1 correlate with immunity, and, therefore, PfEMP-1 may be a good candidate for a malaria vaccine. However, the specificity of CD4 T cells required for a protective variant-specific antibody response is not known. We have measured the CD4 T cell response to 3 different regions that are relatively homologous among different PfEMP-1 variants. The response to the cysteine-rich interdomain region was unusual in that the majority of donors, whether malaria exposed or not, had positive CD4 T cell, interleukin-10, and interferon-gamma responses. The CD4 T cell response to the exon 2 and duffy binding-like domain proteins was significantly greater in malaria-exposed donors than in unexposed Europeans, which suggests that these regions contain peptides recognized by T cells, which thus may be useful as components of a vaccine.